Comparative assessment of long-term survival of patients after primary and recurrent myocardial infarction: a data from the RIMIS registry - S. Yu. Martsevich; O. S. Afonina; A. V. Zagrebelnyy; D. P Sichinava; I. V. Samorodskaya; Yu. V. Avdeev; I. Yu Avdeeva; T. R. Gvindzhilia; I. M. Kuzmina; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To compare the long-term prognosis of life of patients after primary and recurrent acute myocardial infarction (MI).Material and methods. The study was based on the RIMIS registry, which included all patients after transmural MI in 2017 in one of the Moscow vascular centers. The prospective part included 191 patients who survived the acute stage of MI, of which 145 suffered a primary acute MI, 46 — a recurrent acute MI. Long-term follow-up data were collected 71 (53;75) months after discharge from the hospital. The primary endpoint was any-cause death.Results. During the follow-up period, 35 (25,2%) patients with a primary MI and 25 (64,1%) patients with a recurrent MI died (p<0,001). It was not possible to establish the fate of 13 (6,81%) patients, of which 7 (4,83%) were people with primary MI and 6 (13,04%) people with recurrent MI. The death risk was significantly higher in patients who had a recurrent MI compared to patients who had a primary MI: hazard ratio (HR)=3,52 (2,09;5,96), p<0,001). An unfavorable prognosis was determined not by the fact of a recurrent MI, but by the complications that resulted from a previous MI, primarily heart failure, as well as age, sex, smoking status, and hospitalizations for cardiovascular diseases in the year before the reference MI, history of angina and following comorbidities: a prior stroke, major bleeding (life-threatening gastrointestinal bleeding requiring complex surgical intervention). Patients who had a recurrent MI were significantly more adherent to follow-up and prescribed therapy.Conclusion. Despite the modern strategy for treating MI both in the acute stage and in the long-term period, the prognosis after recurrent MI remains unfavorable. Signs negatively affecting the prognosis were sex, age, a history of heart failure and angina pectoris, and hospitalizations for cardiovascular diseases one year prior to reference MI.